2013
DOI: 10.1155/2013/846387
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling Predicts the Existence of Two Functionally Distinct Classes of Ovarian Cancer Stroma

Abstract: Although stromal cell signaling has been shown to play a significant role in the progression of many cancers, relatively little is known about its importance in modulating ovarian cancer development. The purpose of this study was to investigate the process of stroma activation in human ovarian cancer by molecular analysis of matched sets of cancer and surrounding stroma tissues. RNA microarray profiling of 45 tissue samples was carried out using the Affymetrix (U133 Plus 2.0) gene expression platform. Laser ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
1
46
0
3
Order By: Relevance
“…Recently, one study aimed to investigate the molecular changes in OC stroma compared with normal matched tissue. Microarray profiling found significant differences between normal and cancer-associated stroma, as well as two distinct subgroups of cancer-associated stroma: one with similar receptor/ligand expression to the cancer and one different [34]. They indicated that these might be more permissive or resistant to cancer growth and chemoresistance; however, there has been no follow-up on their profiling data to date.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study aimed to investigate the molecular changes in OC stroma compared with normal matched tissue. Microarray profiling found significant differences between normal and cancer-associated stroma, as well as two distinct subgroups of cancer-associated stroma: one with similar receptor/ligand expression to the cancer and one different [34]. They indicated that these might be more permissive or resistant to cancer growth and chemoresistance; however, there has been no follow-up on their profiling data to date.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its composition, the stroma can either impede the neoplastic growth or create the conditions for cell growth and cell migration of cancer cells. Although differing from that in normal ovary tissue, the stroma in ovarian cancer may vary in the expression of genes and production of proteins that ultimately affect tumor growth and invasion . Transcriptome profiling of genes encoding signaling molecules and cognate receptors in ovarian cancer cells and matched stromal cells isolated from patients revealed the existence of two distinct stromal compartments, one permissive and one less prone to support cancer growth .…”
Section: The Prognostic Impact Of Stroma In Ovarian Cancermentioning
confidence: 99%
“…Although differing from that in normal ovary tissue, the stroma in ovarian cancer may vary in the expression of genes and production of proteins that ultimately affect tumor growth and invasion. 32 Transcriptome profiling of genes encoding signaling molecules and cognate receptors in ovarian cancer cells and matched stromal cells isolated from patients revealed the existence of two distinct stromal compartments, one permissive and one less prone to support cancer growth. 32 Noteworthy, the former was associated with grade 3 and the latter with grade 2 ovarian serous adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations